Assessing EFL Teachers’ Intercultural Communicative Competence (ICC) and Intercultural Sensitivity (IS) - Hapsari, Aisyah Indah (RETAIN, 2021)
In the 21st century, it has been the major intent to develop students’ Intercultural Communicative Competence (ICC). Some studies believe that English language teaching must be enhancing students’ intercultural skills in order to be able to communicate properly with people from different language and cultural backgrounds. EFL teachers as key roles in enhancing students’ Intercultural Communicative Competence (ICC) and Intercultural Sensitivity (IS) must be interculturally competent and sensitive. This study aims to investigate the level of EFL teachers’ ICC and IS, and the relationships between ICC and IS. It used a quantitative approach namely experimental survey and correlational study as the research design. Quantitative data were acquired through self-reported questionnaire. There were 73 EFL teachers as the participants of the study. Two questionnaires using AIC (Assessment of Intercultural Competence) ISS (the Intercultural Sensitivity scale) were distributed. The data were administered by using descriptive statistics and Spearman Rank Order Correlation (rho). The findings of this study showed that the EFL teachers had high level of ICC and IS. It also showed that there was a significant relationship between ICC and IS. The implications of these findings as well as suggestions for further research were provided.